Design For Developing A Project Based Learning Model Assisted By The Smartedu Application to Build Knowledge Collaboration In Science Learning - Hadiwijaya Zulkarnaen, Rizki; Islamil, Ali; Mulyani, Hanifah; Chandra, Deni (International Conference on Elementary Education, 2025)
21st century skills are one of the cores in curriculum development that is currently developing. One of the curriculum developments currently occurring is the outcome-based education (OBE) curriculum. The curriculum indicates that learning is not only tied to the content of the concepts studied, but more than that it must be able to produce impacts that can be useful for solving problems in the environment. The indicator components of 21st century skills are closely related to the meaning of this OBE. Technological literacy, collaboration, critical thinking, problem solving and creative thinking are skills that must be developed based on this curriculum. A person’s ability to access technology-based technology and the importance of collaboration in learning activities are unavoidable learning demands. Outcome achievements in learning can be obtained by having a product produced in learning. This is in accordance with the essence of science learning, where the essence of this learning includes processes, attitudes and products. The project based learning (PJBL) model development design assisted by the Smartedu application is an alternative solution developed to overcome these obstacles. Projects produced in learning activities can be packaged in the PJBL model combined with the advantages of smart edu applications. This application was developed with various features that enable synergy in learning so that knowledge collaboration can be formed.